The Concept of the Effectiveness of Awarding Whistleblowers as a Preventive Effort for Narcotics Crimes in the Perspective of Economic Analysis of Law - Tokan, Bebe (International Journal of Law, Environment, and Natural Resources, 2025)
The circulation of illicit narcotics in Indonesia continues to rise despite the existence of comprehensive legal regulations. According to data from the Indonesian National Police (Polri) through the Directorate of Narcotics Crimes (Dittipidnarkoba) and the Regional Police Narcotics Directorates, there were 38,934 cases of illicit narcotics trafficking from January to October 2025. This figure demonstrates that current laws have not been fully effective in suppressing narcotics-related crimes. Therefore, an alternative and more adaptive legal approach is needed, one of which is the Economic Analysis of Law. This study aims to formulate the concept of effectiveness in granting rewards to whistleblowers as a preventive measure in combating narcotics crimes. The research applies a normative juridical method with a legislative approach by examining statutory provisions concerning whistleblower protection and incentives, and evaluating them through an economic perspective to understand how legal rules generate costs, benefits, and behavioral responses within society. The findings indicate an innovative strategy that integrates legal and economic aspects in a balanced manner. Providing financial incentives to whistleblowers is not only a form of recognition for lawful acts but also a rational instrument to encourage greater legal compliance. Such incentives are expected to increase public participation in reporting narcotics crimes, thereby supporting law enforcement efforts. This incentive-based policy has strong potential as an effective preventive measure to promote active community involvement in combating drug trafficking. The study also recommends establishing clear implementation guidelines and periodic evaluation mechanisms to assess the effectiveness of whistleblower incentives in reducing narcotics related offenses.